Cadmium contamination in agricultural soils of China and the impact on food safety. (June 2019) - Wang, Peng; Chen, Hongping; Kopittke, Peter M.; Zhao, Fang-Jie
Abstract: Rapid industrialization in China during the last three decades has resulted in widespread contamination of Cd in agricultural soils. A considerable proportion of the rice grain grown in some areas of southern China has Cd concentrations exceeding the Chinese food limit, raising widespread concern regarding food safety. In this review, we summarize rice grain Cd concentrations in national Chinese markets and in field surveys from contaminated areas, and analyze the potential health risk associated with increased dietary Cd intake. For subsistence rice farmers living in some contaminated areas of southern China who mainly consume locally-produced Cd-contaminated rice, their estimated dietary Cd intake is now comparable to that for the population in the region of Japan where the Itai-Itai disease was first reported. Interventions must be taken urgently to reduce Cd intake for these farmers. We also analyze i) the main reasons causing elevated grain Cd concentrations in southern China, ii) the dominant biogeochemical processes controlling the solubility of Cd in paddy soils, and iii) molecular mechanisms for the uptake and translocation of Cd in rice plants. Based on these analyses, we propose a number of countermeasures to address soil Cd contamination, including i) mitigation of Cd transfer from paddy soils to rice grain, and ii) intervention in those farmers who consume home-grown Cd-contaminated rice. Liming to increase soil pH to 6.5 and gene editing biotechnology are effective strategies to decrease Cd accumulation in rice grain. For these local farmers with high-Cd exposure risk, local governments should monitor the Cd concentration in their home-grown rice and exchange those high-Cd rice with low-Cd rice in order to reduce their dietary Cd intake. Graphical abstract: Image 1 Highlights: We review the status of Cd contamination in soils and rice grain in China. We summarize the biogeochemical processes and molecular tools to produce Cd-safe rice. We propose a number of countermeasures to tackle soil Cd contamination. Interventions are required for the local farmers consuming Cd-contaminated rice. Abstract : This review analyzes the current status of Cd contamination in agricultural soils and rice grain in China and proposes strategies to tackle this issue, including mitigation and intervention measurements.